2021
DOI: 10.1002/jmv.27063
|View full text |Cite
|
Sign up to set email alerts
|

The surveillance of spike protein for patients with COVID‐19 detected in Hong Kong in 2020

Abstract: In 2020, numerous fast‐spreading severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) variants have been reported. These variants had unusually high genetic changes in the spike (S) protein. In an attempt to understand the genetic background of SARS‐CoV‐2 viruses in Hong Kong, especially before vaccination, the purpose of this study is to summarize the S protein mutations detected among coronavirus disease 2019 (COVID‐19) patients in Hong Kong in 2020. COVID‐19 cases were selected every month in 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…This local strain represented the peak of COVID-19 cases detected in Hong Kong between July-August 2020 which was characterized by the 12F amino acid in the spike protein. It was only detected in this specific time interval and then disappeared [12] .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…This local strain represented the peak of COVID-19 cases detected in Hong Kong between July-August 2020 which was characterized by the 12F amino acid in the spike protein. It was only detected in this specific time interval and then disappeared [12] .…”
Section: Resultsmentioning
confidence: 86%
“…They are different from the SARS-CoV-2 strains detected in Hong Kong. Our S gene surveillance [11] showed that these two variants harbored ≥10 non-synonymous substitutions, while the Hong Kong cases sequenced between Jan 2020 to Dec 2020 harbored only a maximum of four non-synonymous substitutions [12] . Since the viral load of clinical specimens for 501Y.V1 were high, serial dilution could be performed and hence, 501Y.V1 was selected in the present study.…”
Section: Methodsmentioning
confidence: 86%
“…For mapping and quantification of the contributions of D614 and G614 viruses in countries, we relied on the tracking Web site () and for the regional geographical distribution within and outside of India we consulted multiple sources. , , , ,, Our study followed the PRISMA guidelines for systematic reviews and meta-analyses . We searched the COVID-19 portfolio of the National Institutes of Health () with the keywords, “anosmia” or “smell” and “India”, “Bangladesh”, “Pakistan” on and before July 22, 2021, resulting in 598 records.…”
Section: Methodsmentioning
confidence: 99%
“…Early detection of SARS-CoV-2 within a population is important for controlling and preventing the spread of COVID-19. In Hong Kong, two peaks of COVID-19 cases were observed before August 2020, namely during March–April 2020 and July–August 2020 [ Mak et al, 2021a ]. In order to eliminate COVID-19 in the community, the Hong Kong Special Administrative Region (HKSAR) government launched the Universal Community Testing Programme (UCTP) on 1 September 2020.…”
Section: Introductionmentioning
confidence: 99%